Magnetic and microwave absorbing properties of BaFe12−2xCoxZnxO19 (x = 0.0; 0.2; 0.4; 0.6) nanocrystalline. (29th June 2018) - Handoko, E; Iwan, S; Budi, Setia; Anggoro, B S; Mangasi, A M; Randa, Maulana; Zulkarnain, Jalil; Kurniawan, C; Sofyan, Nofrijon; Alaydrus, Mudrik
Abstract: We have investigated the magnetic and microwave absorbing properties of barium hexaferrite BaFe12−2x Cox Znx O19 (x = 0.0; 0.2; 0.4; 0.6) nanocrystalline prepared using solid state reaction method. The powder of these ferrites were resulted by high energy ball mill for 1 h and mixed with epoxy resin to be converted into a microwave absorbing composite. The results show barium hexaferrite structures for Ba(Fe, Co, Zn)12 O19 have been formed. The coercive force (Hc) decreases rapidly with the substitution of Co and Zn in the structure of Ba(Fe, Co, Zn)12 O19 . It's indicate that the Co-Zn in the structure of Ba(Fe, Co, Zn)12 O19 contributes to magnetic and microwave absorption properties. The minimum reflection loss value of −29.98 dB was observed at 10.8 GHz with a matching thickness of 1 mm for BaFe12−2x Cox Znx O19 (x = 0.6) nanocrystalline. As results, the magnetic absorbing properties improve significantly by Co-Zn incorporation.